2021
DOI: 10.1021/acsami.1c08331
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Boron-Rich Monolayer BxN as High Capacity for Lithium-Ion Batteries: A First-Principles Study

Abstract: Owing to lightweight, abundant reserves, low cost, and nontoxicity, B-based two-dimensional (2D) materials, e.g., borophene, exhibit great potential as new anode materials with higher energy density for Li-ion batteries (LIBs). However, exfoliation of borophene from the Ag substrate remains the most daunting challenge due to their strong interfacial interactions, significantly restricting its practical applications. In this study, through first-principles swarm-intelligence structure calculations, we have foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 71 publications
2
36
0
Order By: Relevance
“…Since the PBE functional tends to underestimate the band gaps, the HSE06 hybrid functional has been employed to recalculate the band gaps. 49 In Fig. 2(a-d), we use PBE and HSE06 functionals to calculate the energy band and density of states of the SnB monolayer, and the valence bands and high T/PDOS peaks cross the Fermi level, which confirms the electronic conductivity.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…Since the PBE functional tends to underestimate the band gaps, the HSE06 hybrid functional has been employed to recalculate the band gaps. 49 In Fig. 2(a-d), we use PBE and HSE06 functionals to calculate the energy band and density of states of the SnB monolayer, and the valence bands and high T/PDOS peaks cross the Fermi level, which confirms the electronic conductivity.…”
Section: Resultsmentioning
confidence: 66%
“…The E adh of the SnB monolayer is −0.041 eV Å −2 , which is weaker than those of δ 6 -borophene and B 2 N, B 3 N, and B 5 N (−0.070, −0.043, −0.054, and −0.049 eV Å −2 for δ 6 -borophene, B 2 N, B 3 N, and B 5 N). 49 In addition, the adsorption height (2.29 Å) of the SnB monolayer is higher than those of these materials (1.5, 2.1, 2.2, and 2.1 Å for δ 6 -borophene, B 2 N, B 3 N, and B 5 N). This indicates that the SnB monolayer did not form an alloy or surface reconstruction with the Ag (111) substrate.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In this section, we determine their theoretical storage capacity for Li by investigating the amount of Li atom adsorption on the flat boron sheets and the corresponding average adsorption energy. Before that, we define the average adsorption energy ( E ave ) by the following equation E normala normalv normale = ( E B x + n L i E B x + m L i false( n m false) E L i ) / ( n m ) where E normalB x + n normalL normali and E normalB x + m normalL normali are the total energies of n and m ( n > m ) Li atom adsorption on the flat boron sheets, respectively. E Li is the same as in eq .…”
Section: Results and Discussionmentioning
confidence: 99%
“…After decades of development, rechargeable LIBs have achieved great success in clean energy technologies. It can be broadly applied in electric vehicles and electricity grid systems due to their outstanding advantages such as high power density, superior energy efficiency, portability, and so on. Over the years, a large number of research studies have shown that the 2D layered materials with a high-surface area and high electrochemical activity are promising candidates for next-generation LIBs. , Meanwhile, the use of 2D materials as the anode materials for LIBs has been systematically investigated, such as 2D carbon materials, , 2D phosphorene materials, and 2D boron materials. Interestingly, boron serves as the ideal LIB anode materials, getting the highest theoretical capacity (12395 mA h g –1 ) in the form of Li 5 B . However, Li 5 B only exists by forming the structure of atomically isolated B, which makes the storage and release of Li difficult.…”
Section: Introductionmentioning
confidence: 99%